2015
DOI: 10.1093/hmg/ddv211
|View full text |Cite
|
Sign up to set email alerts
|

WNT10A exonic variant increases the risk of keratoconus by decreasing corneal thickness

Abstract: Keratoconus is a degenerative eye condition which results from thinning of the cornea and causes vision distortion. Treatments such as ultraviolet (UV) cross-linking have proved effective for management of keratoconus when performed in early stages of the disease. The central corneal thickness (CCT) is a highly heritable endophenotype of keratoconus, and it is estimated that up to 95% of its phenotypic variance is due to genetics. Genome-wide association efforts of CCT have identified common variants (i.e. min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
0
46
0
2
Order By: Relevance
“…Previous studies have identified the association of CCT with a polymorphic variant in WNT10A in patients with keratoconus 21. However, the genotype-phenotype correlation of MPDZ-NF1B was first discovered in this study, with association of MPDZ-NF1B rs1324183 with corneal thickness and curvature.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have identified the association of CCT with a polymorphic variant in WNT10A in patients with keratoconus 21. However, the genotype-phenotype correlation of MPDZ-NF1B was first discovered in this study, with association of MPDZ-NF1B rs1324183 with corneal thickness and curvature.…”
Section: Discussionmentioning
confidence: 64%
“…1). In the meta-analysis, we excluded 12 of the 36 articles because 7 of them were about gene variants that were not tested in additional independent studies 2733 , 2 reported insufficient genotype data for meta-analysis 34, 35 , 2 were reviews 25, 26 , and 1 was an animal study 36 . We did not receive genotype data after contacting some of the authors 34, 35 .…”
Section: Resultsmentioning
confidence: 99%
“…WNT signaling pathway is essential for normal corneal development and a missense coding variant (rs121908120, c.1145T>A, p.228Phe>Ile) in the WNT10A gene has been associated with KC risk 72 . Moreover, using RNA-Seq, a recent study showed dysregulation in WNT signaling in the KC-affected corneal epithelium.…”
Section: Mace Et Al Have Shown Anti-proliferative and Hyper-apoptotimentioning
confidence: 99%